(untitled) (Research, Society and Development, 2021)
Introduction: Fibromyalgia syndrome is a chronic idiopathic condition of generalized musculoskeletal pain that mainly affects women. The aim of this study is to investigate in the literature the effects of aquatic interventions in fibromyalgia in relation to physical and psychological parameters, and the main assessment methods. Methods: A literature search was carried out in Embase, PubMed and Scielo databases with the descriptors: Fibromyalgia, Fibromyalgia Syndrome, Aquatic exercise and Water exercise, total of 23 articles. Results: Aquatic therapies are recommended as a treatment for their benefits. Immersion in water allows the reproduction of movements in a safe and varied way, minimizing impacts when compared to exercises on the ground. Fibromyalgia patients report the sensation of relaxation and relief of symptoms, after the practice of activity in an aquatic environment. Conclusion: Aquatic interventions are presented as efficient therapeutic resources to treat pain and improve the quality of life of people with fibromyalgia.